Two Hadra Hydriae in the Collection of the Patriarchal Sacristy in Alexandria - Savvopoulos, Kyriakos (Journal of Hellenistic Pottery and Material Culture, 2017)
Hadra hydriae have been seen by many scholars as being emblematic of the necropolis of Alexandria, since they represent a type of funerary urn that was widely used in the Hellenistic city. Their name refers to the site of the Hadra cemetery, situated to the east of Alexandria. This was one of the earliest sites to be systematically excavated (1883 –1884), resulting in the discovery of a substantial number of funerary urns of this type1. Since then, Hadra hydriae have been discovered in other cemeteries in the western and eastern parts of the city. However, they are not exclusive to Alexandria. Hadra hydriae have been found in several places across the Hellenistic eastern Mediterranean—in Cyprus, Rhodes, Athens and also Crete, which appears to have been a major centre of production for this type of urn2. Still, there is a strong association with the history and society of the city of Alexander, based on written evidence inscribed on the surface of a few dozen Hadra hydriae, indicating name, status or even profession of their occupants3. On the basis of the inscribed examples, Hadra hydriae are dated to the 3rd and 2nd centuries BCE. Other hydriae-type urns were used in Alexandrian cemeteries throughout the Hellenistic period.